Patient empowerment in cancer pain management: an integrative literature review. Issue 11 (12th May 2014) - te Boveldt, Nienke; Vernooij‐Dassen, Myrra; Leppink, Irene; Samwel, Han; Vissers, Kris; Engels, Yvonne
Abstract Objective More than 50% of patients with cancer experience pain. Patient empowerment has been highlighted as central to success in pain management. Up to now, no clear model for this patient group exists, yet several strategies to empower patients have been used in clinical practice. This review examines how empowerment or related concepts have been described in relation to pain management in patients with cancer. With the help of a conceptual model, recommendations for clinical practice are provided. Methods An integrative review was conducted, using the databases PubMed, CINAHL and PsycINFO. We evaluated papers discussing empowerment or related concepts in relation to pain management in patients with cancer. We analyzed the term 'empowerment' semantically. Results From a total of 5984 identified papers, 34 were included for analysis. Empowerment has been described with the concepts self‐efficacy, active patient participation, increasing abilities, and control of life. Most papers focus on pain treatment induced by the professional caregiver or on the active involvement of the patient, and not on the combination of both. The following elements of empowerment could be discriminated: role of the patient, role of the professional, resources, self‐efficacy, active coping, and shared decision making. Conclusions On the basis of these findings, we propose a conceptual model to empower patients in controlling cancer pain. We recommend focusing on pain treatment given by the professional, on the active involvement of the patient, and on the interaction of both. Our model might also be useful for other patient groups or specific contexts, especially in symptom management. Copyright © 2014 John Wiley & Sons, Ltd.